Myocardial epithelial inclusions in a Holstein calf - Ceribasi, A. O.; Ceribasi, S.; Ozkaraca, M.; Ozer, H. (Shiraz Univ, 2012)
Epithelial inclusions were detected in myocardium of a 2-month-old male Holstein calf. Microscopically, nonpurulent myocarditis along with focal tubular and acinar structures covered with cuboidal epithelial cells was seen in the myocardium. Most tubular and acinar structures stained with Masson's trichrome were found to be surrounded with a dense collagen. Tubular and acinar structures had PAS positive basement membrane. Immunohistochemical staining revealed that tubular and acinar structures were both vimentin and pancytokeratin positive, while the connective tissue was only vimentin positive.
Keywords: Calf; Epithelial inclusion; Heart